THE IMPLEMENTATION OF CHARACTERISTICS OF ORGANIZATIONAL CULTURE “SHARING” BASED ON LOCAL WISDOM IN INCREASING HR COMPETENCE IN INDONESIA (FACING ASIAN FUTURE SHOCK 2020) - Mulyaningsih Mulyaningsih (Kopertis Region IV Jabar and Banten, 2019)
Indonesia as the country with the opportunity cost of investment and the highest corruption in ASIA business caused a cultural and population changes which is affect to family structure in the development business and state. Based on those conditions, Indonesia must change fast become count country in ASIA to build character through local knowledge possessed a vast country and large The shift in the pattern of the surviving members of regional communities is an indicator of impending shocks to the mindset, ways of thinking, feeling and reacting based on the environment and the condition of the demands of the behavior of the members together are embraced and accepted by the organization to act and solve problems, adapt and unites members of the organization through a shift in values, norms and cultural rules significantly (mean) the impact of the shock towards the life of the nation both by employers and stakeholders organizations in Indonesia. ASIA development of the business sector in the 21st century emphasizes ethical investment. Ethical investments In the 21st century, supporting ethical organization, including in developed countries the problem of ethics and organizational behavior into consideration when deciding policies and financial. The idea of ethical investment had various depend on each country, and company cultural perception. The application of ethical investment strategies of individual, non-profit organizations, governments and companies to attract potential investors, in the hope that the fund is managed in a way that does not have a negative impact on society, including Indonesian society. The influence of cultural, social and geographical had very strong impact to employers and stakeholders behavior. The diversity behavior is fundamental basic considered in fundamentals treatment will support the success of Indonesia development over this years. It will deal with the honesty, integrity in the right employees, strong leadership and support for ethnic behavior. Those conditions would cause a shock to the human resources therefore need nation quality recovery in national policies circle in order to determine direction of attitudes change and nation view as an interactive consequence in organizational culture characteristic which is owned Indonesian HR should be able to function as a tool to support the implementation of the development progress through employee competence and leadership. The Indonesian efforts to increase capacity and competence of the Human Resources (HR) with respect to resilience in the face of 2020, namely the implementation of a characteristic of organization culture that will affect the way work is done and how employees behave based on the philosophy of Pancasila and the results of research in the form of build character first through local wisdom in the sunda level; like